ANALISIS PELATIHAN KARYAWAN PADA UNIT BUMI KEPANDUAN SENTUL BOGOR - Arif Luqman Ibrahim Sutarno; Awa Awa (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This research was conducted at Unit Bumi Kepanduan Sentul Bogor, a company operating in camping ground services. The main issue identified is that employee training has not been implemented optimally, particularly regarding the relevance of training materials and the availability of training facilities, which affects service quality. This study aims to examine the implementation of employee training and identify existing problems. The research employed a descriptive qualitative approach with data collected through observation, interviews, literature study, and documentation. The findings indicate that training programs have been conducted but have not yet achieved optimal results due to unsuitable training materials and limited training facilities. Therefore, improvements in training content and facilities are necessary to enhance employee service quality.